The Role of Amicus Curiae in Influencing The Confidence of Judges in The Supreme Court and Constitutional Court - Benni Mangiring Ompusunggu (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Recently, the topic of Amicu Curiae has become a hot topic of discussion among the legal observer community. On the one hand, the Amicus Curiae is of the opinion that it can significantly influence the judge's confidence, but on the other hand, it is of the opinion that the Amicus Curiae cannot influence it because there are other factors that influence it, namely the facts of the trial. This research is qualitative research with a descriptive approach, namely describing Amicus Curiae, its history, meaning, and its role in influencing judges' beliefs. The data used in this research is secondary data that researchers obtained from statutory regulations, books, scientific articles, and other things that are usually used in qualitative research. These data were analyzed using the stages of data collection, data selection, data reduction, data analysis, and drawing conclusions. The result in this article show that the position of Amicus Curiae is only limited to opinions from scientific articles and opinions scattered on social media. The difference is that this specification is addressed to the Constitutional Court judges before making a decision. However, specifically personally, this could influence the judge's psychology to remind him of things that happened in the trial and carefully pay attention to the two different perspectives. Amicus Curiae also consists of various types of varied sentences. If it is related to the decision of the Constitutional Court in resolving disputes over the results of the 2024 Presidential and Vice Presidential General Election, there are things that are different compared to the decision on resolving disputes over the results of the previous year's Presidential and Vice Presidential General Election, where there are 3 judges who took dissenting opinion decisions compared to five other judges. . It is possible that this difference is caused by one of the factors due to the existence of the 24 Amicus Curiae.